Unexpected detours and reactivity encountered during the planned synthesis of hypervalent 10–Pn–3 species (Pn = P or As). (15th March 2018) - Hyvl, Jakub; Yoshida, Wesley Y.; Moore, Curtis E.; Rheingold, Arnold L.; Cain, Matthew F.
Graphical abstract: The planned synthesis of hypervalent 10–P–3 and 10–As–3 compounds 1 and 2 from brominated bis(oxazoline) and bis(imine) NCN pincers via a lithiation/electrophilic quenching (with PnCl3 ; Pn = P or As)/reduction protocol resulted in unexpected findings and reactivity. Generation of bis(oxazoline)-ligated (NCN)PCl2 derivative CP resulted in an intramolecular SN 2 reaction, leading to formation of ring-opened 3, which could be phenylated with PhMgBr to give 4 . In solution, bis(imine)-based (NCN)PCl2 analogue DP displayed a complicated product mixture by 31 P 1 H NMR spectroscopy, likely due to the presence of several ionic species and iminium-enamine tautomers, while the As derivative (DAs ) was isolable and crystallized in a distorted square pyramidal geometry. Reduction of both derivatives of D with PMe3 did not afford the targeted 10–Pn–3 (Pn = P or As) species 2, but rather generated rare examples of dynamic bell-clappers. Abstract: The planned synthesis of hypervalent 10–P–3 and 10–As–3 compounds 1 and 2 from brominated bis(oxazoline) and bis(imine) NCN pincers via a lithiation/electrophilic quenching (with PnCl3 ; Pn = P or As)/reduction protocol resulted in unexpected findings and reactivity. Generation of bis(oxazoline)-ligated (NCN)PCl2 derivative CP resulted in an intramolecular SN 2 reaction, leading to formation of ring-opened 3, which could be phenylated with PhMgBr to give 4 . In solution, bis(imine)-based (NCN)PCl2 analogue DP displayed a complicated product mixture by 31 P 1 H NMR spectroscopy, likely due to the presence of several ionic species and iminium-enamine tautomers, while the As derivative (DAs ) was isolable and crystallized in a distorted square pyramidal geometry. Reduction of both derivatives of D with PMe3 did not afford the targeted 10–Pn–3 (Pn = P or As) species 2, but rather generated rare examples of dynamic bell-clappers.